The Concept Of Liability As Legal Protection For Notaries Exercising Authority In Indonesia - Kirana, Claradyta; Maryano, Maryano; Akkapin, Supaphorn (CV. Era Digital Nusantara, 2024)
This research examines the legal protection for notaries in exercising their authority, especially when there are allegations of errors in making deeds that can have an impact on criminal or civil lawsuits. The phenomenon of increasing lawsuit cases against notaries indicates the existence of legal uncertainty in this profession, which encourages the urgency of formulating a clearer concept of legal protection. Using the theory of liability, this research analyses the limits of notary responsibility as well as the concept of legal protection that can provide prevention against unfounded claims. This research uses normative legal research methods with statutory, case, and conceptual approaches. The results show that notaries need legal protection that can balance their duties and authorities, especially in relation to the limits of liability and the application of liability. The proposed concept of legal protection covers two aspects, namely preventive and repressive, to ensure that notaries can perform their duties independently and are safe from excessive legal threats. The conclusion of this research is expected to contribute to the formation of legal policies that strengthen protection for notaries and clarify the role of the state in providing guarantees to the integrity of the notary profession in Indonesia.